Interaction of Digital Art, Space and Memory: The Case of Alkazar Movie Theater - Erbay, Muteber (Journal of Visual Art and Design, 2024)
The pursuit of new art formed by the integration of digital technologies with art is used in many areas of architecture, such as facades, surfaces, showcases, and interiors. The use of art together with the technological infrastructure, especially on interior surfaces, has enabled artists to develop their limits of creativity. In this sense, one dimension of creativity is the designs made through the memory of space. This study focused on how digital artworks produced through the memory of space are applied in the Alkazar Movie Theater in Beyoğlu, Istanbul and their effect on the user. At the point of transferring social memory, Refik Anadol’s work titled Alkazar Dream, renowned for its visualization of memory through digital art, has been effective. The study examined how this interaction was achieved, using a descriptive-analytical and qualitative data analysis method. As a result of the study, the effect of experiencing space and social memory through digital art on the user was revealed. It was found that the interaction of the user with digital art as a viewer and participant is an effective method for the preservation and transfer of social memory into the future.